Policies and policy processes of the European Union - Buonanno, Laurie; Nugent, Neill (Basingstoke, Hampshire [England] ; New York : Palgrave MacMillan, 2013)
'This major new text on EU policy-making provides a concise but systematic introduction to the main policy areas in which the EU is active and the way in which EU policy is made, explaining how and why the EU's policy portfolio has developed as it has and the distinctive characteristics of each broad policy area'--Publisher's website.
Introduction -- The Policy Portfolio -- Understanding the Policy Portfolio -- The Principal Policy Institutions -- Other Important Policy Actors -- Key Features of Policy Processes -- The Policy Cycle -- Policy-Making Modes -- The Internal Market -- Building a Socio-Economic Union : Agriculture, Cohesion, Environment and Growth Policies -- Economic and Monetary Union -- The Area of Freedom, Security and Justice -- Trade Policy -- Foreign and External Security Policy -- The Budget -- Achievements, Challenges and Prospects.
Includes bibliographical references (pages 329-349) and index.
Keywords: European Union; European Union; Political planning -- European Union countries; Policy sciences -- European Union countries; UE/CE Union europnne; UE/CE Institutions et organes; UE/CE Politique; UE/CE Marchunique; UE/CE JAI = Justice et affaires intieures; UE/CE PESC= Politique range et de suritcommune; Politics and Government; Economic policy; Policy sciences; Political planning; Social policy; Politics and Government; European Union countries -- Economic policy; European Union countries -- Social policy; Europe -- European Union countries